Local path planning for mobile robots based on intermediate objectives. Issue 4 (May 2015) - Ma, Yingchong; Zheng, Gang; Perruquetti, Wilfrid; Qiu, Zhaopeng
SUMMARY This paper presents a path planning algorithm for autonomous navigation of non-holonomic mobile robots in complex environments. The irregular contour of obstacles is represented by segments. The goal of the robot is to move towards a known target while avoiding obstacles. The velocity constraints, robot kinematic model and non-holonomic constraint are considered in the problem. The optimal path planning problem is formulated as a constrained receding horizon planning problem and the trajectory is obtained by solving an optimal control problem with constraints. Local minima are avoided by choosing intermediate objectives based on the real-time environment.